Content Analysis of Value in Islamic Education Textbooks for Eighth and Tenth Grade in Jordan and the Extent to which they are Appropriate to Criteria Derived from the Amman Message - Odat, Tameem (Jordan Journal of Educational Sciences, 2009)
This study aimed to analyze Islamic Education Textbooks for eighth and tenth grade in Jordan and identfy values included in them and whether they are appropriate to Criteria derived from the Amman Message. The sample of the study consisted of Islamic Education Textbooks for 8th and 10th grades in jordan in the school year 2006/2007.To achieve the purpose of the study, the researcher selected the analytic descriptive method depending on the paragraph as a unit for analysis. The researcher also prepared a list of criteria derived from the Amman message. Then the researcher analyzed the content of the Islamic Education textbooks in light of these criteria One of the most important results that the study revealed was having 65 criteria from Amman message that were used in the Islamic Education textbooks and it showed that Islamic Education textbooks concern with the Amman message was not enough which indicated that the Amman message was not taken into consideration in the process of writing these textbooks. Based on these results, it is recommended to design more descriptive and experimental studies for all stages and reconsider the process of writing the Islamic education textbooks by taking into consideration the Amman message as one of the basic sources in designing and developing it.